Heart Disease Mortality in the United States, 1970 to 2022 - Sara J. King; Tenzin Yeshi Wangdak Yuthok; Adrian M. Bacong; Abha Khandelwal; Dhruv S. Kazi; Michael E. Mussolino; Sally S. Wong; Seth S. Martin; Eldrin F. Lewis; Fatima Rodriguez; Latha P. Palaniappan (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background Studying trends in mortality is essential to advance understanding of population health. Further evaluation of long‐term heart disease mortality trends and subtypes in the United States is needed to guide public health and clinical interventions. Methods This study used the National Vital Statistics System Centers for Disease Control and Prevention Wide‐Ranging Online Data for Epidemiologic Research data for adults aged 25 years and older in the United States from 1970 to 2022. Outcomes included absolute number and age‐adjusted mortality of total heart disease, ischemic heart disease, and other heart disease subtypes. Results From 1970 to 2022, overall age‐adjusted heart disease mortality decreased by 66% from 1970 to 2022 (from 761 to 258 per 100 000). In 1970, 91% of all heart disease deaths were ischemic, declining to 53% of all heart disease deaths in 2022. From 1970 to 2022, age‐adjusted mortality decreased by 89% for acute myocardial infarction (from 354 to 40 per 100 000) and 81% for all ischemic heart disease (from 693 to 135 per 100 00). In contrast, from 1970 to 2022 age‐adjusted mortality for other heart disease subtypes increased by 81% (from 68 to 123 per 100 000), with the greatest increases in heart failure (146% increase), hypertensive heart disease (106% increase) and arrhythmias (450% increase). Conclusions Heart disease mortality has decreased over the past 5 decades. There is an increasing burden of mortality from other heart conditions including heart failure, hypertensive heart disease, and arrhythmias. Further efforts must be undertaken to address the growing challenge of these other heart conditions.